Quantum electrodynamics in the strong pulsed laser fields - Roshchupkin, S.P. (Вопросы атомной науки и техники, 2013)
The some results on the resonant processes of quantum electrodynamics (QED) proceeding in the strong pulsed light fields, realized in modern powerful pulsed lasers is presented. The appearance of resonances in a laser field is one of the fundamental problems of QED in electromagnetic fields. Following QED processes of the second order in the fine structure constant in the pulsed laser field are considered: resonant spontaneous bremsstrahlung by an electron scattered by a nucleus, resonant photocreation of electron{positron pairs on a nucleus, and resonant scattering of a lepton by a lepton. The resonant peak's altitude and width are defined by the external pulsed wave properties. It is demonstrated that the resonant cross sections may be several orders of magnitude greater than the corresponding cross sections in the absence of an external field. Results obtained may be experimentally verified, for example, by the scientific facilities at the SLAC National Accelerator Laboratory and FAIR (Facility for Antiproton and Ion Research, Darmstadt, Germany). Розглядаються деякi резонанснi процеси квантової електродинамiки (КЕД), що протiкають у сильних iмпульсних свiтлових полях, реалiзованих у сучасних потужних iмпульсних лазерах. Поява резонансiв у лазерному полi є однiєю з фундаментальних проблем КЕД в електромагнiтних полях. Розглядаються наступнi процеси КЕД другого порядку зi сталої тонкої структури в iмпульсному лазерному полi: резонансне спонтанне гальмове випромiнювання електрона, розсiянного на ядрi; резонансне фотона-родження електрон-позитронних пар на ядрi й резонансне розсiювання лептона на лептонi. Амплiтуда й ширина резонансних пiкiв визначаються параметрами зовнiшньої iмпульсної хвилi. Показано, що резонанснi поперечнi перерiзи можуть надекiлька порядкiв величини бути бiльше, нiж вiдповiднi поперечнi перерiзи у вiдсутностi зовнiшнього поля. Отриманi результати можуть бути експериментально перевiренi в наукових об’єднаннях, таких як SLAC (National Accelerator Laboratory) i FAIR (Facility for Antiproton and Ion Research, Darmstadt, Germany). Рассматриваются некоторые резонансные процессы квантовой электродинамики (КЭД), протекающие в сильных импульсных световых полях, реализуемых в современных мощных импульсных лазерах. Появление резонансов в лазерном поле является одной из фундаментальных проблем КЭД в электро-магнитных полях. Рассматриваются следующие процессы КЭД второго порядка по постоянной тонкой структуры в импульсном лазерном поле: резонансное спонтанное тормозное излучение электрона, рассеянного на ядре; резонансное фоторождение электрон-позитронных пар на ядре и резонансное рассеяние лептона на лептоне. Амплитуда и ширина резонансных пиков определяются параметрами внешней импульсной волны. Показано,что резонансные поперечные сечения могут быть на несколько порядков величины больше,чем соответствующие поперечные сечения в отсутствие внешнего поля. Полученные результаты могут быть экспериментально проверены в научных коллоборациях, таких как SLAC(National Accelerator Laboratory) и FAIR (Facility for Antiproton and Ion Research, Darmstadt, Germany).